A meta-analysis of the interactive effects of UV and drought on plants - Jansen, Marcel A K; Ač, Alexander; Klem, Karel; Urban, Otmar (Plant, cell & environment, 2022)
Interactions between climate change and UV penetration in the biosphere are resulting in the exposure of plants to new combinations of UV radiation and drought. In theory, the impacts of combinations of UV and drought may be additive, synergistic or antagonistic. Lack of understanding of the impacts of combined treatments creates substantial uncertainties that hamper predictions of future ecological change. Here, we compiled information from 52 publications and analysed the relative impacts of UV and/or drought. Both UV and drought have substantial negative effects on biomass accumulation, plant height, photosynthesis, leaf area and stomatal conductance and transpiration, while increasing stress-associated symptoms such as MDA accumulation and reactive-oxygen-species content. Contents of proline, flavonoids, antioxidants and anthocyanins, associated with plant acclimation, are upregulated both under enhanced UV and drought. In plants exposed to both UV and drought, increases in plant defense responses are less-than-additive, and so are the damage and growth retardation. Less-than-additive effects were observed across field, glasshouse and growth-chamber studies, indicating similar physiological response mechanisms. Induction of a degree of cross-resistance seems the most likely interpretation of the observed less-than-additive responses. The data show that in future climates, the impacts of increases in drought exposure may be lessened by naturally high UV regimes.
Keywords: Acclimatization; additive effect; Droughts; listy rostlin; Plant Transpiration; Biomass; cross-resistance; období sucha; průduchy rostlin; Photosynthesis; Ultraviolet Rays; Plant Leaves; aklimatizace; fotosyntéza; fyziologie rostlin; Plant Physiological Phenomena; Plant Stomata; transpirace rostlin; biomasa; synergistic effect; ultrafialové záření; stress